Cinacalcet versus Parathyroidectomy in the Treatment of Secondary Hyperparathyroidism Post Renal Transplantation - Soliman Amin R.; Maamoun Hoda A.; Soliman Mahmoud A.; Darwish Hatem; Elbanna Esam (Sciendo, 2016)
Background. Persistent hyperparathyroidism (HPT) with hypercalcemia is prevalent after transplant and is considered a risk factor for progressive bone loss and fractures and vascular calcification, as well as the development of tubulointerstitial calcifications of renal allografts and graft dysfunction. The subtotal parathyroidectomy is the standard treatment, although currently it has been replaced by the calcimimetic cinacalcet.